Task-specific training versus usual care to improve upper limb function after stroke: the “Task-AT Home” randomised controlled trial protocol - van Vliet, Paulette; Carey, Leeanne Mary; Turton, Ailie; Kwakkel, Gert; Palazzi, Kerrin; Oldmeadow, Christopher; Searles, Andrew; Lavis, Heidi; Middleton, Sandy; Galloway, Margaret; Dimech-Betancourt, Bleydy; O'Keefe, Sophie; et al. (Frontiers in Neurology, 2023)
Background Sixty percent of people have non-functional arms 6 months after stroke. More effective treatments are needed. Cochrane Reviews show low-quality evidence that task-specific training improves upper limb function. Our feasibility trial showed 56 h of task-specific training over 6 weeks resulted in an increase of a median 6 points on the Action Research Arm test (ARAT), demonstrating the need for more definitive evidence from a larger randomised controlled trial. Task-AT Home is a two-arm, assessor-blinded, multicentre randomised, controlled study, conducted in the home setting. Aim The objective is to determine whether task-specific training is a more effective treatment than usual care, for improving upper limb function, amount of upper limb use, and health related quality of life at 6 weeks and 6 months after intervention commencement. Our primary hypothesis is that upper limb function will achieve a ≥ 5 point improvement on the ARAT in the task-specific training group compared to the usual care group, after 6 weeks of intervention. Methods Participants living at home, with remaining upper limb deficit, are recruited at 3 months after stroke from sites in NSW and Victoria, Australia. Following baseline assessment, participants are randomised to 6 weeks of either task-specific or usual care intervention, stratified for upper limb function based on the ARAT score. The task-specific group receive 14 h of therapist-led task-specific training plus 42 h of guided self-practice. The primary outcome measure is the ARAT at 6 weeks. Secondary measures include the Motor Activity Log (MAL) at 6 weeks and the ARAT, MAL and EQ5D-5 L at 6 months. Assessments occur at baseline, after 6 weeks of intervention, and at 6 months after intervention commencement. Analysis will be intention to treat using a generalised linear mixed model to report estimated mean differences in scores between the two groups at each timepoint with 95% confidence interval and value of p. Discussion If the task-specific home-based training programme is more effective than usual care in improving arm function, implementation of the programme into clinical practice would potentially lead to improvements in upper limb function and quality of life for people with stroke. Clinical Trial Registration ANZCTR.org.au/ACTRN12617001631392p.aspx